DC motor controller using DC converter / Muhammad Khiruddin Abdullah - Abdullah, Muhammad Khiruddin (1997)
This project describe the development of the D.C Motor controller using computer controlled four-quadrant chopper unit for both clockwise and counter-clockwise rotation applications. The computer generated pulse width modulation (PWM) pattern is used to control the firing sequence of the transistors in the chopper circuit. The system is designed to have high output power and simple control structure, with very fast current response and instantaneous power reversal capability. Also it operation is almost insensitive to dc input voltage unbalances. The software and hardware developed provide suitable tools for research or teaching in electrical machine.